Enhancing Students’ Literacy Skills through the use of English Storybooks - I Putu Andre Suhardiana; Ni Luh Gede Windy Lestari (Yavana Bhasha : Journal of English Language Education, 2020)
Basically, education holds a huge influence on the outcome of the students in the process of learning. One obstacle in education today is concerning students’ literacy skill. Most of them possess a low interest in literacy. The strategy that can be adopted to enhance students’ literacy is through the use of storybooks. Numerous storybooks and various activities are provided in order to solve this difficulty, particularly in English education as a foreign language. The storybook can simplify the understanding of the foreign language. The stories are educational materials that provide effective learning with reality, recognition, and entertainment. The objective of this study is to enhance the literacy skills of students by using English storybooks, specifically for young learners and accommodate the widest opportunity for teachers to develop their English teaching abilities in such a way that in the future they are better prepared and alert in dealing with the identical situations.